Postoperative Endophthalmitis caused by Escherichia coli and Burkholderia cepacia complex: A Rare Case Report - Thakali, Ashwin; Sitaula, Ranju Kharel; Karki, Pratap; Pant, Aashish Raj (Journal of Institute of Medicine Nepal, 2025)
Endophthalmitis is one of the most serious complications following cataract surgery. Early treatment with intravitreal antibiotics with or without pars plana vitrectomy is the standard management but gram-negative bacteria and multi-drug resistant bacteria pose significant challenges as the prognosis is usually poor in such cases. We present a case of post-operative endophthalmitis following cataract surgery caused by multi-drug resistant Escherichia coli as well as Burkholderia cepacia complex.  The patient was treated first with intravitreal antibiotics, then with core vitrectomy and intravitreal antibiotics. Intraocular lens explantation was also done at a later stage since there was no improvement.